Nonculprit Lesion Plaque Morphology in Patients With ST-Segment–Elevation Myocardial Infarction: Results From the COMPLETE Trial Optical Coherence Tomography Substudys. (July 2020) - Pinilla-Echeverri, Natalia; Mehta, Shamir R.; Wang, Jia; Lavi, Shahar; Schampaert, Erick; Cantor, Warren J.; Bainey, Kevin R.; Welsh, Robert C.; Kassam, Saleem; Mehran, Roxana; Storey, Robert F.; Nguyen, Helen; et al.
Abstract : Background: Complete revascularization with routine percutaneous coronary intervention of nonculprit lesions after primary percutaneous coronary intervention improves outcomes in ST-segment–elevation myocardial infarction. Whether this benefit is associated with nonculprit lesion vulnerability is unknown. Methods: In a prospective substudy of the COMPLETEs trial (Complete vs Culprit-Only Revascularization to Treat Multi-Vessel Disease After Early PCI for STEMI), we performed optical coherence tomography of at least 2 coronary arteries before nonculprit lesion percutaneous coronary intervention in 93 patients with ST-segment–elevation myocardial infarction and multivessel disease; and the ST-segment–elevation myocardial infarction culprit vessel if there was unstented segment amenable to imaging. Nonculprit lesions were categorized as obstructive (≥70% stenosis by visual angiographic assessment) or nonobstructive, and as thin-cap fibroatheroma (TCFA) or non-TCFA by optical coherence tomography criteria. TCFA was defined as a lesion with mean fibrous cap thickness <65 μm overlying a lipid arc >90°. Results: On a patient level, at least one obstructive TCFA was observed in 44/93 (47%) of patients. On a lesion level, there were 58 TCFAs among 150 obstructive nonculprit lesions compared with 74 TCFAs among 275 nonculprit lesions (adjusted TCFA prevalence: 35.4% versus 23.2%, P =0.022). Compared with obstructive non-TCFAs, obstructive TCFAs had similar lesion length (23.1 versus 20.8 mm, P =0.16) but higher lipid quadrants (55.2 versus 19.2, P <0.001), greater mean lipid arc (203.8° versus 84.5°, P <0.001), and more macrophages (97.1% versus 54.4%, P <0.001) and cholesterol crystals (85.8% versus 44.3%, P <0.001). For nonobstructive lesions, TCFA lesions had similar lesion length (16.7 versus 14.6 mm, P =0.11), but more lipid quadrants (36.4 versus 13.5, P <0.001), and greater mean lipid arc (191.8° versus 84.2°, P <0.001) compared with non-TCFA. Conclusions: Among patients who underwent optical coherence tomography imaging in the COMPLETE trial, nearly 50% had at least one obstructive nonculprit lesion containing complex vulnerable plaque. Obstructive lesions more commonly harbored vulnerable plaque morphology than nonobstructive lesions. This may help explain the benefit of routine percutaneous coronary intervention of obstructive nonculprit lesions in patients with ST-segment–elevation myocardial infarction and multivessel disease. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01740479s. Abstract : Supplemental Digital Content is available in the text.